Mutagenesis and digital image analysis of mutants for quality attributes of native Cynodon dactylon - TIWARI, AJAI KUMAR; KUMAR, RAMESH; KUMAR, GUNJEET; KADAM, GANESH B; SAHA, T N; S, GIRISH K; TIWARI, BHARAT (The Indian Journal of Agricultural Sciences, 2014)
The ability to capture information of turf grass in situ makes digital camera based image analysis, a viable tool to quantify turf grass (Cynodon dactylon Pers.) in field experiments. In addition to colour quantification, digital image analysis has been used successfully to quantify percentage turf grass cover and has also been proved to be useful in quantifying turf parameters such as weed infestation, disease incidence, herbicide toxicity, leaf area and recovery from injury. Colour is one of the major criteria used to evaluate the quality of turf and lawn. To generate variability in Bermuda grass to select genotypes responsive to low management, gamma-ray irradiation was used for induction of dwarfness and other quality attributes. Five dwarf mutant lines (DFR 440, DFR-C-444, DFR-C-445, DFR-C 446 and DFR-C-448) were isolated. In the present study, camera and image analysis technique is applied to measure turf colour by its reflectance in the HSB colour scale. The data depicts that the dwarf mutant lines had better quality of lower canopy height, shorter internodes and shorter leaves than the parent. It is demonstrated that image analysis is a suitable non-destructive tool to assess turf grass colour in a reproducible and calibrated manner, over a wide span of structural and colour attributes of turf grass.